ChatGPT and artificial intelligence the future of healthcare? - Robinson, Jared; Banerjee, Indrajit; Atterbury, Todd; Banerjee, Indraneel; Leclézio, Alexandra (Nepal Mediciti Medical Journal, 2023)
Artificial intelligence is an upcoming branch of computer science, with applications across the world in each and every industry. The launch of ChatGPT- an advanced and easily accessible machine learning and artificial intelligence application will alter the manner in which both the medical fraternity, research and global healthcare sectors are trained and operate. ChatGPT was launched on the 30th of November 2022, by a San Francisco based software company (OpenAI). ChatGPT is a cutting-edge language model (chatbot) which forms part of the (Generative Pre-trained Transformer) group of software. The powerful inbuilt language model allows the generated response to be humanoid in nature and not to be perceived as being AI generated and therefore attaches a greater innate value to the resultant text, thereby negating the need to re-read and re-write the generated text. The model has multiple advantages across medical education, research, patient treatment and monitoring. As with all technology and models of this nature, innate disadvantages are evident; predominantly in the realm of data security and medicolegal difficulties. ChatGPT is an extremely powerful tool, with limitless capabilities and shall most certainly be useful in optimizing our daily lives and routines. The scope for such powerful artificial intelligence is undeniable and will most certainly gain traction within the medical sector. The healthcare sector will however demand a higher level of refinement and an AI model more specifically designed by and for the healthcare sector before the large-scale implementation thereof within the field will be accepted and viable.